Evaluation of the heel external rotation test in soft tissue deficiencies associated with adult acquired flatfoot deformity (AAFD). A cadaver sectioning analysis. (May 2023) - West, Cavan; Norrish, Alan; Brassett, Cecilia; Pasapula, Chandra
Abstract: Background: To date, evaluation of the heel external rotation test has not been taken with respect to AAFD. Traditional 'gold standard' tests do not account for the contribution of the midfoot ligaments towards instability. These tests would be flawed as any midfoot instability may produce a false positive result. Aims: To evaluate the differential contribution of the spring, deltoid and other local ligaments in external rotation generated at the heel. Methods: Serial ligament sectioning was performed on 16 cadaveric specimens, with a 40 N-external rotation force applied to the heel. These were divided into four groups with different sequences of ligament sectioning. Measurements of the total amount/range of external, tibiotalar and subtalar rotation were made. Results: The deep component of the deltoid ligament (DD) was the main ligament influencing heel external rotation ( P < 0.05, in all cases), and acted primarily at the tibiotalar joint (87.9 %). The spring ligament (SL) influenced heel external rotation predominantly (91.2 %) at the subtalar joint (STJ). Greater than 20 degrees external rotation could only be achieved with DD sectioning. The interosseous (IO) and cervical (CL) ligaments did not significantly contribute to external rotation at either joint ( P > 0.05). Conclusion: Clinically relevant external rotation (>20 degrees) is solely attributable to DD failure in the presence of intact lateral ligaments (LL). This test may improve detection of DD instability and allow clinicians to subclassify patients with Stage 2 AAFD into those where DD may or may not be compromised. Highlights: Modified application of heel external rotation test detects deep deltoid instability in AAFD. Spring ligament sectioning causes non-significant increase in tibiotalar external rotation. Deep deltoid is the only medial ligament, when sectioned, to cause significant tibiotalar external rotation.